STRATEGI PENINGKATAN DAYA SAING USAHA KECIL BERBASIS OLAHAN IKAN DI DESA SUMBER JAYA KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - Suharmi, Suharmi; Ayuni, Rossa; Ocpi, Sucita (Jurnal Economic Edu, 2020)
The study aimed atfinding out the strategy of increasing competitiveness of small business based on fish processing in Sumber Jaya Village Kampung Melayu Subdistrict Bengkulu City. The study employed a qualitative descriptive method. Further, the study utilized data and sources of data, primary data and secondary Data. Primary data includes data obtained directly by researchers without any intermediaries. Data was gained through carrying out interviews and direct observation of traditional fish managers in Sumber Jaya Village, Kampung Melayu subdistrict, Bengkulu City. Secondary data taken are written sources such as the problems studied, namely the strategy of increasing the competitiveness of processed fish. Data collection was conducted through observation, interviews, documentation. Data analysis consisted of data collection, data reduction, data presentation, conclusion drawing. Based on the results of the study in Sumber Jaya Market, Kampung Melayu subdistrict, Bengkulu City, the results of the study were achieved namely: Based on fish processing competitiveness strategies, both dried fish and smoked fish, several problems can be grouped into three, namely (1) in terms of product, retrieval of raw materials like fresh fish; (2) in terms of processing, including: cleanliness and hygiene of the products produced; (3) in terms of marketing, including: price differences, product hygiene, controlling the market and coordinating with market traders. Keywords: Strategy, Competitiveness, Small Business in Sumber Jaya Village